2013
DOI: 10.1055/s-0033-1349367
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Survival of a Fetus with Intestinal Volvulus and Intussusception: A Case Report and Review of the Literature

Abstract: Fetal intestinal volvulus is a rare life-threatening condition. Late diagnosis of volvulus contributes to high rate of morbidity and mortality. It has variable degrees of presentation and survival. Intrauterine volvulus may be complicated by intestinal atresia due to ischemic necrosis. To our knowledge, there are three reported cases of term fetal demise. We report a case of fetal intestinal volvulus with perinatal survival of the largest term infant described with this complication to date. The volvulus was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Volvulus is usually a postnatal complication of GS that may cause intestinal atresia due to mechanical obstruction and ischemic necrosis of the bowel [42]. In our cohort study, 4 volvulus cases were detected antenatally and confirmed at birth, of whom 3 died after birth.…”
Section: Discussionmentioning
confidence: 84%
“…Volvulus is usually a postnatal complication of GS that may cause intestinal atresia due to mechanical obstruction and ischemic necrosis of the bowel [42]. In our cohort study, 4 volvulus cases were detected antenatally and confirmed at birth, of whom 3 died after birth.…”
Section: Discussionmentioning
confidence: 84%
“…Infant was delivered by cesarean section for repetitive late decelerations, and preoperative diagnosis was made by upper GI series with contrast but no MRI was done. 20 Immediate surgical management of these cases is life saving and delay in diagnosis can be fatal. Preterm delivery and surgical intervention should be considered when the diagnosis is made prenatally.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal volvulus is a rare condition in which the small bowel and proximal colon twist around the superior mesenteric artery. This occurs when the intestinal loop that is suspended along the free margin of the mesentery twists around the anterior mesentery artery [ 8 10 ]. Between the eighth and tenth weeks of gestation, malrotation of the fetal gut occurs when the elongating intestine returns to the abdominal cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Between the eighth and tenth weeks of gestation, malrotation of the fetal gut occurs when the elongating intestine returns to the abdominal cavity. Between the sixth and tenth weeks, the midgut loop rotates 90 degrees counterclockwise around the axis of the superior mesenteric artery [ 8 10 ]. This brings the duodenal jejunal loop to the right and the ileocolic loop to the left side.…”
Section: Introductionmentioning
confidence: 99%